Beyond artificial academic debates: for a diverse, inclusive, and impactful ethnobiology and ethnomedicine - Victoria Reyes-García (BMC, 2023)
Abstract In answer to the question "Should ethnobiology and ethnomedicine more decisively foster hypothesis-driven forefront research able to turn findings into policy and abandon more classical folkloric studies?", in this essay I argue that a major strength of ethnobiology and ethnomedicine is their ability to bridge theories and methods from the natural sciences, the social sciences, and the humanities. Hypothesis-driven research is a powerful way to structure thinking that can lead to forefront research findings. But hypothesis-driven research is not the only way to structure thinking and is not a necessary condition to impact policymaking. To increase policy impact, ethnobiology and ethnomedicine should continue nurturing a mixture of complementary methods and inclusive approaches as fragmentation through opposing different approaches might weaken the discipline. Moreover, with the aim to play a fundamental role in building bridges between different knowledge systems and co-producing solutions towards sustainability, the discipline could benefit from enlarging its epistemological grounds through more collaborative research. Ethnobiologists' research findings, hypothesis-driven, descriptive, or co-constructed can become leverage points to transform knowledge into actionable outcomes in different levels of decision-making.